Bitcoin and ESG 2 - Finger, Maya (Henry Stewart Talks, 2023)
Accessibility, inclusion and diversity in Bitcoin, Bitcoin governance, Social aspects of Bitcoin, Individual sovereignty, Transparency and privacy, Flexibility and anonymity